Optima Nutrition: A Tool for Enhancing the Efficiency of Nutrition Spending - Shekar, Meera (2018)
Meera Shekar IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand